Rulership in 1st to 14th century Scandinavia. Royal graves and sites at Avaldsnes and beyond - Skre, Dagfinn (Ergänzungsbände zum Reallexikon der Germanischen Altertumskunde, 2020)
This book discusses the 3rd-11th century developments that led to the formation of the three Scandinavian kingdoms in the Viking Age. Wide-ranging studies of communication routes, regional identities, judicial territories, and royal sites and graves trace a complex trajectory of rulership in these pagan Germanic societies. In the final section, new light is shed on the pinnacle and demise of the Norwegian kingdom in the 13th-14th centuries.